The Temperate Deciduous Forests of the Northern Hemisphere. A review - Loidi, Javier; Marcenò, Corrado (Mediterranean Botany, 2022)
Temperate Deciduous Forests occur almost exclusively in the northern hemisphere and thrive under temperate climate with cold winter and warm-humid summer. They covered a continuous belt during most of the Tertiary across the continent Laurasia occupying a large area in higher latitudes. With the cooling of the Earth’s climate and the appearance of the subtropical aridity areas, in combination with the separation of North America from Eurasia, this continuous area split into the three mainly existing now: Eastern North America, Western Eurasia and Eastern Asia. The tree flora reveals the common origin of the three current areas and the events causing more or less severe extinctions during the cold periods of the Pleistocene, in combination with the mountain uplift did happen since the Miocene affected differently to them. The basic features of the deciduous trait and its likely origin are discussed, as well as the ecologic implications of such a trait. For further research, the current possibilities provided by available vegetation datasets (EVA, sPlot) opens the possibility of using a large mass of vegetation plots data involving most of the vascular flora of these forests in order to find out insights about their origin and evolution over time as well as their links with current or past environmental conditions.
Keywords: Temperate forest biota; decidiousness; Arcto-Tertiary flora; evergreeness; Western Eurasia; Eastern North America; Eastern Asia